ASSA13-02-25 CARTO Three-Dimensional Mapping System Guided Catheter Ablation of Macro-Reentrant Atrial Tachycardia Following Cardiac Surgery in Patients with Structural Heart Disease. (29th April 2013) - Shu-Yin, Shi; Zu-Lu, Wang; Yan-Chun, Liang; Ming, Liang; Ya-Ling, Han; Zhi-Qing, Jin; Shi-Bei, Li; Hong, Zhang
Abstract : Background: Because radiofrequency catheter ablation of macro-reentrant atrial tachycardia (AT) following cardiac surgery of structural heart disease had a low successful rate and a high recurrence, we aimed to explore a successful method to solve this problem. Objective: This study was to investigate the electrophysiological mechanisms and radiofrequency catheter ablation of macro-reentrant atrial tachycardia (AT) following cardiac surgery of structural heart disease, and to test the success rate by using CARTO electroanatomic mapping. Methods: A total of 20 patients (16 men, aged 35 ± 13.5 years) in ShenyangNorthernHospitalwere studied. After determining the mechanism of macro-reentrant AT, the electroanatomic structures of the right or/and left atria during AT were constructed by using CARTO electroanatomic mapping system. To combine the results of entrainment mapping, the possible reentrant circuits of AT were analysed and the ablation lines were defined. The saline irrigated radiofrequency ablation catheter was used for ablation in all the 20 patients. Results: In the 20 patients, 16 patients had 1 form of AT and 4 patients had 2 forms. Twenty-four forms were all macro-reentrant AT confirmed by CARTO system electroanatomic mapping and entrainment. Among the 24 forms of AT, 18 forms were typical atrial flutter of the right atrium, 5 forms were incisional reentrant AT of the right atrium, and 1 form was macro-reentrant AT around the mitral annulus. Eighteen of the 20 patients had a successful ablation, including 17 of 18 forms of typical atrial flutter of the right atrium and 4 of 5 forms of incisional reentrant AT of the right atrium. During the follow-up of 12 months on the average, 17 patients with a successful ablation had no recurrence, and only 1 patient recurred as atrial fibrillation. Conclusions: CARTO three-dimensional mapping system guided catheter ablation of macro-reentrant atrial tachycardia following cardiac surgery in patients with structural heart disease had a high success rate and a low recurrence rate.